2013
DOI: 10.1093/pcp/pct122
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Transcription Factors Involved in Rice Secondary Cell Wall Formation

Abstract: Using co-expression network analysis, we identified 123 transcription factors (TFs) as candidate secondary cell wall regulators in rice. To validate whether these TFs are associated with secondary cell wall formation, six TF genes belonging to the MYB, NAC or homeodomain-containing TF families were overexpressed or downregulated in rice. With the exception of OsMYB58/63-RNAi plants, all transgenic plants showed phenotypes possibly related to secondary cell wall alteration, such as dwarfism, narrow and dark gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
87
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 33 publications
5
87
0
1
Order By: Relevance
“…The switchgrass ortholog in this clade with gene expression data available, AP13ISTG56055 , shows high expression in E4 vascular bundles and internodes, consistent with the possibility that they regulate SCW biosynthesis (Figure 9). Overexpression of the two OsMYB58/63 genes was recently found to promote lignin deposition in rice stems, supporting their orthologous relationship with the AtMYB58 and 63 [75]. In the OrthoMCL analysis, AtMYB58 and AtMYB63 are paralogs and putative co-orthologs are found in the grasses.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…The switchgrass ortholog in this clade with gene expression data available, AP13ISTG56055 , shows high expression in E4 vascular bundles and internodes, consistent with the possibility that they regulate SCW biosynthesis (Figure 9). Overexpression of the two OsMYB58/63 genes was recently found to promote lignin deposition in rice stems, supporting their orthologous relationship with the AtMYB58 and 63 [75]. In the OrthoMCL analysis, AtMYB58 and AtMYB63 are paralogs and putative co-orthologs are found in the grasses.…”
Section: Resultsmentioning
confidence: 68%
“…Sequence identity between AtMYB103 and the putative grass orthologs is intermediate, ranging from 48% to 51%, and OrthoMCL mostly supports the phylogenetic analysis, further evidence that AP13ISTG58495 may be a SCW regulator in switchgrass (Table 4). In rice, a preliminary study reported that RNAi lines of OsMYB103 show a severe dwarf phenotype and did not grow to maturity [75]; whereas, only altered tapetum, pollen and trichome morphology were observed in Arabidopsis AtMYB103 silencing mutants [28,29]. This difference in phenotypes caused by expression disruption of apparently orthologous genes between rice and Arabidopsis suggests differences in the SCW regulatory network between grasses and dicots not obvious from the phylogenetic relationships of the Class I proteins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This discrepancy indicates that the secondary wall regulatory network in monocot plants may be distinct from the one in dicots in certain respects. In this study, although total lignin content was not changed in the transgenic plants, we cannot exclude the possibility that their lignin composition was altered, as Os-NAC31 and Os-MYB61 were reported to regulate Os-MYB46 and Os-CINNAMYL ALCOHOL DEHYDROGENASE2 expression (Zhong et al, 2011;Hirano et al, 2013). Moreover, cellulosic biofuel is a type of sustainable energy source that has gained popular support due to its potential benefit to the global environment.…”
Section: Potential Value Of This Regulatory Pathway In Crop and Biomamentioning
confidence: 75%